In Vivo Imaging of the Tumor‐Associated Enzyme NCEH1 with a Covalent PET Probe. Issue 35 (15th June 2020) - Chang, Jae Won; Bhuiyan, Mohammed; Tsai, Hsiu‐Ming; Zhang, Hannah J.; Li, Gang; Fathi, Shaghayegh; McCutcheon, David C.; Leoni, Lara; Freifelder, Richard; Chen, Chin‐Tu; Moellering, Raymond E.
Abstract: Herein, we report the development of an 18 F‐labeled, activity‐based small‐molecule probe targeting the cancer‐associated serine hydrolase NCEH1. We undertook a focused medicinal chemistry campaign to simultaneously preserve potent and specific NCEH1 labeling in live cells and animals, while permitting facile 18 F radionuclide incorporation required for PET imaging. The resulting molecule, [ 18 F]JW199, labels active NCEH1 in live cells at nanomolar concentrations and greater than 1000‐fold selectivity relative to other serine hydrolases. [ 18 F]JW199 displays rapid, NCEH1‐dependent accumulation in mouse tissues. Finally, we demonstrate that [ 18 F]JW199 labels aggressive cancer tumor cells in vivo, which uncovered localized NCEH1 activity at the leading edge of triple‐negative breast cancer tumors, suggesting roles for NCEH1 in tumor aggressiveness and metastasis. Abstract : A Covalent PET probe : An 18 F‐labeled, activity‐based small molecule probe, [ 18 F]JW199, potently and selectively targets NCEH1 in live cells and displays rapid, NCEH1‐dependent accumulation in mouse tissues and tumor xenografts.